Angiographic suppression of the artery of Adamkiewicz by venous hypertension resolving after embolization in a case of spinal epidural arteriovenous fistula. (15th July 2014) - Eckart Sorte, Danielle; Pardo, Carlos A; Gailloud, Philippe
Abstract : A case of complete angiographic suppression of the artery of Adamkiewicz and anterior spinal artery in a patient with a spinal epidural arteriovenous fistula (AVF) is reported. Slow flow AVFs typically present with progressive myelopathy secondary to spinal venous hypertension (SVH). The lack of a normal venous phase during angiography and its restoration after treatment is commonly observed with these lesions, yet a similar phenomenon seems exceptional at the arterial level. Right T11 intercostal artery angiograms obtained before and after treatment of a left L4 epidural AVF documented the initial suppression of the artery of Adamkiewicz and anterior spinal artery, and their normal appearance immediately after correction of the SVH by embolization. This report confirms that SVH can angiographically suppress prominent and functionally important spinal arteries, re-emphasizing the potential role played by secondary arterial changes in SVH induced myelopathy. This hemodynamic phenomenon also represents a potential pitfall during diagnostic and therapeutic endovascular procedures.